Pendidikan Toleransi Berbasis Etika Profetik - Hayati, Noor; Supena, Ilyas (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
Educational and religious institutions should be a place for seeding tolerance. But in reality, there are many hate teachings and speech that lead to intolerance and radicalism. In turn, it will endanger the stability and integrity of Indonesia. This study aims to present the formulation of tolerance education in Kuntowijoyo's prophetic ethics perspective. This article is a literature research uses philosophical as well as historical approach. This article uses multiple approach. In collecting data, the author uses the documentation method. The results of this article are first, the roots of intolerant and radical attitudes are from certain groups that massively campaign for hate teachings and speech with certain goals. Second, the need for providing comprehensive understanding of tolerance education. Third, the formulation of tolerance education uses prophetic ethical perspective. that is the essence of all religion teachings; humanization, liberation, and transcendence.